Detached eddy simulation of turbulent flow around square and circular cylinders on Cartesian cut cells. (1st May 2016) - Bai, W.; Mingham, C.G.; Causon, D.M.; Qian, L.
Abstract: Square and circular cylinders in three-dimensional turbulent flows are studied numerically using the LES and DES turbulence models. One aim of the present study is to implement the LES and DES turbulence models in a cell-centered finite volume method (FVM) developed for solving the Navier–Stokes equations on Cartesian cut cells. The Cartesian cut cell approach is known to be robust for problems in geometrically complex domains with fixed or moving boundaries. For the purpose of validating the present numerical model, the current flow past fixed square and circular cylinders at moderate Reynolds numbers is tested first. Comparison of the computed results with experimental data reveals that the DES models are superior to the conventional LES and RANS models. The second aim of the present study is to assess the performance of different RANS based DES turbulence models. By means of the comparison of results obtained with the 0-equation mixing-length, 1-equation S–A and 2-equation k – ω based DES models for the flow over the same circular cylinder, some recommendations are proposed. According to the present study, in terms of accuracy the 1-equation S–A based DES model is very promising. Beside this, if the computational cost is the main concern, the 0-equation mixing-length based DES model might be an ideal option, achieving a good balance between accuracy and efficiency. Highlights: Various turbulence models are implemented in a Navier–Stokes solver on Cartesian cut cell grids. Comparison reveals that DES models are superior to conventional turbulence models, especially for coarse mesh. Different RANS based DES models are compared through the case of flow past a circular cylinder. The promising DES turbulence models are recommended based on the comparison.